Dimensions of variability in northern Khoekhoe language and culture - Rapold, C. J.; Widlok, T. (Southern African Humanities, 2021)
This article takes an interdisciplinary route towards explaining the complex history of Hai//om culture and language. We begin this article with a short review of ideas relating to ’origins’ and historical reconstructions as they are currently played out among Khoekhoe groups in Namibia, in particular with regard to the Hai//om. We then take a comparative look at parts of the kinship system and the tonology of ?Âkhoe Hai//om and other variants of Khoekhoe. With regard to the kinship and naming system, we see patterns that show similarities with Nama and Damara on the one hand but also with ’San’ groups on the other hand. With regard to tonology, new data from three northern Khoekoe varieties shows similarities as well as differences with Standard Namibian Khoekhoe and Ju and Tuu varieties. The historical scenarios that might explain these facts suggest different centres of innovations and opposite directions of diffusion. The anthropological and linguistic data demonstrates that only a fine-grained and multi-layered approach that goes far beyond any simplistic dichotomies can do justice to the Hai//om riddle. To cite this article: Rapold, C.J. & Widlok, T. 2008. Dimensions of variability in northern Khoekhoe language and culture. Southern African Humanities 20: 133-61.